Directional out-coupling efficiency enhancement of organic light-emitting devices by a microlens array. (1st January 2013) - Shen, Su; Zhou, Fang; Wei, Guojun; Pu, Donglin; Zhou, Yun
Microlens arrays film fabricated by ultra-violet (UV) roll-to-roll nanoimprinting lithography is introduced on glass substrate to directionally coupling the efficiency of organic light-emitting devices (OLEDs). The microlenses suppress wave guiding loss in the substrate and a theoretical model, based on Monte-Carlo model, is developed to simulate the enhancement effects. The numerical results show that ellipsoidal-like microlens array can not only increase the efficiency by a factor of more than 35%, but also directionally couple output light with the luminance density distribution along the orthogonal directions compressed by 10 degrees. Such a microlens array mould is fabricated by a combination of DMD-based laser direct writing lithography and thermal reflow method, followed by electroforming for transferring the surface structure to a nickel plate. The obtained mould is wrapped on a roller for the mass production of microlens array film by UV roll-to-roll nanoimprinting process. OLED attached with such microlens array film with a maximum increase of 35% in efficiency is achieved and directional out-coupling phenomenon can be observed experimentally. Such a directional out-coupling microlens array film can be used in OLED to enhance the luminous intensity efficiency and save power consumption for future lighting and display application.